2022
DOI: 10.1172/jci150517
|View full text |Cite
|
Sign up to set email alerts
|

MERTK activation drives osimertinib resistance in EGFR-mutant non–small cell lung cancer

Abstract: Acquired resistance is inevitable in non–small cell lung cancers (NSCLCs) treated with osimertinib (OSI), and the mechanisms are not well defined. The MERTK ligand GAS6 promoted downstream oncogenic signaling in EGFR -mutated ( EGFR MT ) NSCLC cells treated with OSI, suggesting a role for MERTK activation in OSI resistance. Indeed, treatment with MRX-2843, a first-in-class MERTK kinase inhibitor, resensitized GAS6-treated NSCLC cells to OSI. Both GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 74 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…MerTK is expressed in both immune and non-immune cells and is involved in inflammation, metabolism, and vascular homeostasis [20]. Previous studies have indicated that MerTK protects against liver fibrosis and cancer [21][22][23]. The expression of MerTK in 13 the sciatic nerve and serum of rats was detected via immunohistochemistry, immunofluorescence, western blotting, and ELISA methods in our study, which showed that MerTK was upregulated in the T2DM and DPN groups, and the expression of MerTK was significantly increased in the DPN group than in the CON and T2DM groups, which is consistent with the results of our previous study [10].…”
Section: Discussionmentioning
confidence: 99%
“…MerTK is expressed in both immune and non-immune cells and is involved in inflammation, metabolism, and vascular homeostasis [20]. Previous studies have indicated that MerTK protects against liver fibrosis and cancer [21][22][23]. The expression of MerTK in 13 the sciatic nerve and serum of rats was detected via immunohistochemistry, immunofluorescence, western blotting, and ELISA methods in our study, which showed that MerTK was upregulated in the T2DM and DPN groups, and the expression of MerTK was significantly increased in the DPN group than in the CON and T2DM groups, which is consistent with the results of our previous study [10].…”
Section: Discussionmentioning
confidence: 99%
“…MERTK inhibitors have been confirmed to be used in combination with radiotherapy or chemotherapy in glioma, NSCLC, head and neck squamous cell carcinoma, and other tumors to achieve better efficacy [30][31][32]. In addition, ERO1A, PKP2, and MERTK have been proved to promote the progress and drug resistance of NSCLC by enhancing the activation of tumor and PI3K, EGFR, and other signal pathways [33][34][35]. In this study, we identified the good prognosis prediction effect of this risk model and confirmed this prediction effect using chemotherapy patients in the GSE42127 dataset as a validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal LINC00313 produced by lung cancer cells also promotes M2 polarization of macrophages and lung tumor growth in vivo [ 75 ]. Advanced NSCLC is frequently treated with osimertinib, an irreversible third-generation tyrosine kinase inhibitor (TKI) of the epidermal growth factor receptor (EGFR) [ 76 ]. LncRNA SOX2 overlapping transcript (SOX2-OT) is concentrated in exosomes isolated from H1975 cells.…”
Section: Exosomal Ncrnas Regulate Macrophage-linked Intercellular Com...mentioning
confidence: 99%